The relationship between horizontal and vertical plyometric jumps with sprint acceleration - Coh, M.; Bubanj, S.; Kreft, R.; Rautar, S. (Facta Universitatis: Series Physical Education and Sport, 2021)
The aim of the study was to determine the correlation between horizontal and vertical plyometric jumps with sprint acceleration (SA) in sprint distances of 10 and 30 meters. Six horizontal and six vertical plyometric tests were used with 44 male and 22 female trained athletes of different sports. A correlation analysis was used to determine the association between horizontal and vertical plyometric jumps with SA. The results showed a greater degree of correlation between horizontal plyometric tasks and SA than vertical plyometrics. The number of correlations of horizontal and vertical jumps with SA was significantly higher in the male subsample. For male participants, the highest correlation coefficients of two unilateral horizontal single-leg jumps could be determined for the 10-meter sprint (r=-.542; r=-.465), as well as the 30-meter sprint (r=-617; r=-.617). In the female subsample, unilateral single-leg jumps had statistically insignificant correlations with sprint speed, except for the 30-meter sprint test (r=-.641). Significant correlations to SA in both subsamples also included the standing triple jump and the bounce triple jump - 25 cm. The standing triple jump results for women showed the highest correlation with SA across all tests (r=-.663). Horizontal bilateral jumps, horizontal double-leg jumps, and the standing long jump had an important correlation with the results of the 30-meter sprint. Starting acceleration for very short distances is a very complex motor task, which depends not only on the strength of the lower extremities, but also largely on inter-muscle coordination, running biomechanics, and undoubtedly, the morphological constitution of the athlete.